Time-dependent changes in glucose and insulin regulation during intermittent hypoxia and continuous hypoxia - Lee, Euhan J. (2012)
Hypoxia manifests in many forms including the short repetitive intermittent hypoxia (IH) of sleep apnoea and the continuous hypoxia (CH) of altitude, both of which may impact metabolic function. Based on our own previous studies and the available literature, we hypothesized that whereas acute exposure to IH and CH would lead to comparable metabolic dysfunction, with longer-term exposure, metabolism would normalize to a greater extent with CH than IH. Studies were conducted in lean C57BL/6J mice exposed to either IH or CH for 1 day or 4 weeks and compared to either intermittent air (IA) or unhandled (UN) controls, respectively. We utilized the frequently sampled intravenous glucose tolerance test and minimal model analyses to determine insulin-dependent (insulin sensitivity; S(I)) and insulin-independent (glucose effectiveness; S(g)) glucose disposal, as well as the insulin response to glucose (acute insulin response to glucose; AIR(g)). Our data show that 1-day exposure impaired the glucose tolerance and caused reductions in S(g) and AIR(g) in both the IH and CH groups, but only IH caused a significant decrease in S(I) (7.5 ± 2.7 vs. 17.0 ± 5.3 μU ml(−1) min(−1); p < 0.05). After 4-week exposure, there was evidence of metabolic adaptation in both hypoxic groups, however, in the CH group, there was a supranormal increase in S(I) relative to both UN and IH groups. We conclude that in lean mice, the marked metabolic dysfunction that occurs with acute exposure to hypoxia is reversed to a greater extent with chronic CH exposure than chronic IH exposure.